2016
DOI: 10.1371/journal.pone.0159348
|View full text |Cite|
|
Sign up to set email alerts
|

Arabidopsis thaliana Contains Both Ni2+ and Zn2+ Dependent Glyoxalase I Enzymes and Ectopic Expression of the Latter Contributes More towards Abiotic Stress Tolerance in E. coli

Abstract: The glyoxalase pathway is ubiquitously found in all the organisms ranging from prokaryotes to eukaryotes. It acts as a major pathway for detoxification of methylglyoxal (MG), which deleteriously affects the biological system in stress conditions. The first important enzyme of this system is Glyoxalase I (GLYI). It is a metalloenzyme which requires divalent metal ions for its activity. This divalent metal ion can be either Zn2+ as found in most of eukaryotes or Ni2+ as seen in prokaryotes. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 27 publications
(31 reference statements)
5
50
0
Order By: Relevance
“…Four SbGLYI proteins namely, SbGLYI-7, SbGLYI-10, SbGLYI-11 and SbGLYI-14, were found to be Ni 2+ -dependent showing greater homology to the previously characterised Ni 2+dependent GLYI proteins from rice and Arabidopsis [42,43] and having a similar domain length, of approximately 120 aa. Similarly, only one GLYI protein namely, SbGLYI-8 was found to be Zn 2+ -dependent, having a domain length of 140 aa, much like rice OsGLYI-8 [44] and Arabidopsis AtGLYI-2 [43,45] proteins. Interestingly, SbGLYI-8 possessed two spliced forms coding for almost similar length proteins (214 and 227 aa long), and both were predicted to be similarly localised in the mitochondria and/or chloroplast.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Four SbGLYI proteins namely, SbGLYI-7, SbGLYI-10, SbGLYI-11 and SbGLYI-14, were found to be Ni 2+ -dependent showing greater homology to the previously characterised Ni 2+dependent GLYI proteins from rice and Arabidopsis [42,43] and having a similar domain length, of approximately 120 aa. Similarly, only one GLYI protein namely, SbGLYI-8 was found to be Zn 2+ -dependent, having a domain length of 140 aa, much like rice OsGLYI-8 [44] and Arabidopsis AtGLYI-2 [43,45] proteins. Interestingly, SbGLYI-8 possessed two spliced forms coding for almost similar length proteins (214 and 227 aa long), and both were predicted to be similarly localised in the mitochondria and/or chloroplast.…”
Section: Discussionmentioning
confidence: 86%
“…The metal specificity of SbGLYI proteins was predicted based on their domain sequence and length [40,41]. Four SbGLYI proteins namely, SbGLYI-7, SbGLYI-10, SbGLYI-11 and SbGLYI-14, were found to be Ni 2+ -dependent showing greater homology to the previously characterised Ni 2+dependent GLYI proteins from rice and Arabidopsis [42,43] and having a similar domain length, of approximately 120 aa. Similarly, only one GLYI protein namely, SbGLYI-8 was found to be Zn 2+ -dependent, having a domain length of 140 aa, much like rice OsGLYI-8 [44] and Arabidopsis AtGLYI-2 [43,45] proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The decline was more severe (about 13.5‐fold) in the cytoplasmic fraction, where three AtGLYI‐2 isoforms were found to be localized, as compared with the nuclear fraction which showed a two‐fold decline in GLYI activity (Figure i,j). The GLYI activity in the atglyI‐2 plants did not change significantly in response to salt treatment (Figure i,j), thereby suggesting that AtGLYI‐2 is involved in maintaining increased GLYI activity in plants under saline conditions, as its loss fails to enhance the otherwise observed increase in GLYI activity under salinity stress (Jain et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…However, further study revealed that only three Arabidopsis thaliana genes (AtGLYI2, AtGLYI3 and AtGLYI6) and two rice genes (OsGLYI8 and OsGLYI11.2) were functional and contained all the binding sites required for glyoxalase activity. In addition, the activity of AtGLYI2 was dependent on Zn 2+ , while the activities of AtGLYI3, AtGLYI6 and OsGLYI11.2 were dependent on Ni 2+ [11][12][13]. Specifically, OsGLYI-8 did not show any strict requirement for a metal ion for its activity [14].…”
Section: Introductionmentioning
confidence: 91%